The fight against poverty : policy options and reality - Bussmann, Uwe (Diplomica Verlag, 2011)
HauptbeschreibungDid you know that 13.5 percent of people in the total population in Germany lives below the poverty line? Most of people don't know that! Poverty in Germany is a largely unknown issue. But it exists! Even more concerning: 16.5 % of all German households are threatened by poverty as well. What can politicians do to help those people? Are there any political options at all?In this assignment we first would like to inform about poverty in general and in Germany in particular. Second, we show that policy options exist and third how these measures take hold in practise.€Biogra.